The Brothers Grimm and the making of German nationalism - Norberg, Jakob, 1975- (Cambridge University Press, 2022)
In the first comprehensive English-language portrait of Jacob and Wilhelm Grimm as political thinkers and actors, Jakob Norberg reveals how history's two most famous folklorists envisioned the role of literary and linguistic scholars in defining national identity. Convinced of the political relevance of their folk tale collections and grammatical studies, the Brothers Grimm argued that they could help disentangle language groups from one another, redraw the boundaries of states in Europe, and counsel kings and princes on the proper extent and character of their rule. They sought not only to recover and revive a neglected native culture for a contemporary audience, but also to facilitate a more harmonious and enduring relationship between the traditional political elite and an emerging national collective. Through close historical analysis, Norberg reconstructs how the Grimms wished to mediate between sovereigns and peoples, politics and culture. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Grimm, Jacob, -- 1785-1863 -- Political and social views.; Grimm, Wilhelm, -- 1786-1859 -- Political and social views.; Philologists -- Biography.; Nationalism and literature -- Germany -- History -- 19th century.; Germany -- Intellectual life -- 19th century.